A comprehensive characterization of empirical parameterizations for OH exposure in the Aerodyne Potential Aerosol Mass Oxidation Flow Reactor (PAM-OFR) - Q. Liu; Q. Liu; Q. Liu; D. D. Huang; A. T. Lambe; S. Lou; L. Zeng; L. Zeng; Y. Wu; C. Huang; S. Tao; X. Cheng; et al. (Atmospheric Measurement Techniques)
The oxidation flow reactor (OFR) has been widely used to simulate secondary organic aerosol (SOA) formation in laboratory and field studies. OH exposure (OHexp), representing the extent of hydroxyl (OH) radical oxidation and normally expressed as the product of OH concentration and residence time in the OFR, is important in assessing the oxidation chemistry in SOA formation. Several models have been developed to quantify the OHexp in OFRs, and empirical equations have been proposed to parameterize OHexp. Practically, the empirical equations and the associated parameters are derived under atmospheric relevant conditions (i.e., external OH reactivity) with limited variations in calibration conditions, such as residence time, water vapor mixing ratio, and ozone (O3) concentration. Whether the equations or parameters derived under limited sets of calibration conditions can accurately predict the OHexp under dynamically changing experimental conditions with large variations (i.e., extremely high external OH reactivity) in real applications remains uncertain. In this study, we conducted 62 sets of experiments (416 data points) under a wide range of experimental conditions to evaluate the scope of the application of the empirical equations to estimate OHexp. Sensitivity tests were also conducted to obtain a minimum number of data points, which is necessary for generating the fitting parameters. We showed that, for the OFR185 mode (185 nm lamps with internal O3 generation), except for external OH reactivity, the parameters obtained within a narrow range of calibration conditions can be extended to estimate the OHexp when the experiments are in wider ranges of conditions. For example, parameters derived within a narrow water vapor mixing ratio range (0.49 %–0.99 %, corresponding to 15.1 %–30.8 % of relative humidity at 101.325 kPa and 298 K) can be extended to estimate the OHexp under the entire range of water vapor mixing ratios (0.49 %–2.76 %, equivalent to 15.1 %–85.7 % of relative humidity under identical conditions). However, the parameters obtained when the external OH reactivity is below 23 s−1 could not be used to reproduce the OHexp under the entire range of external OH reactivity (4–204 s−1). For the OFR254 mode (254 nm lamps with external O3 generation), all parameters obtained within a narrow range of conditions can be used to estimate OHexp accurately when experimental conditions are extended. Additionally, when using the OFR254 mode, lamp voltages that are too low should be avoided, as they will generally result in large deviations in the estimations of OHexp from empirical equations. Regardless of whether the OFR185 or OFR254 mode is used, at least 20–30 data points from sulfur dioxide (SO2) or carbon monoxide (CO) decay with varying conditions are required to fit a set of empirical parameters that can accurately estimate OHexp. Caution should be exercised to use fitted parameters from low external OH reactivity to high ones, for instance, those from direct emissions such as vehicular exhaust and biomass burning.